Efficiency of Three Extracted Herbs on Inhibition of Vibrio harveyi and Vibrio parahaemolyticus - Wongwuttiwat, Krisanee; Wongwuttiwat, Sakda; Chuaytong, Anusorn; Midcadee, Maimunoh; Petratmunee, Chaiwat (Journal of Vocational Education in Agriculture, 2022)
Vibrio harveyi and Vibrio parahaemolyticus have been the most common group of pathogenic bacteria affecting shrimp farming industry in Thailand. The use of antibiotics, as a solution, could result in antibiotic residues in aquaculture products. This study aimed to determine the minimum inhibitory concentration (MIC) and compare inhibition efficiency of three extracted herbs on V. harveyi and V. parahaemolyticus using agar well diffusion method. There were five treatments with three replications including Tropical Almond, Guava and The Creat leaf extracts diluted in 95 % methanol at 50, 25, 12.5 and 6.25 % concentration as well as distilled water and oxytetracyclin as negative and positive control respectively. The study results showed the same MIC values (6.25 %) amomg treatments. Besides, the results in efficiency comparison found that Tropical Almond (13.25±0.55 มม.) and Guava extracts (13.50±1.58 มม.) showed the significant higher inhibition efficiency on V. harveyi than The Creat extract at 50 % concentration (P<0.05). Moreover, Tropical Almond showed the significant highest inhibition efficiency (12.55±2.68 มม.) on V. parahaemolyticus at 25 % concentration (P<0.05). The results indicated that both extracted herbs; Tropical Almond and Guava could be antibiotic substitutes for V. harveyi and V. parahaemolyticus inhibition, even though zone of inhibition found smaller than oxytetracyclin, because of decrease in both production cost and residues